“Luminescência de compostos de Eu3+: uma prosposta de ensino, conceitos, modelos e linguagens” - Escremin, João Vicente (2008)
The luminescence, that consists of the irradiation of the light to low temperatures, is very present in the daily of the people, as in the illuminated streets of a great city, in the plates of signalling of the highways or in the green light of a lightning bug, for example However, through the analysis of works involving the luminescence of Eu3+ accepted for presentation in five Annual Meetings of the Brazilian Society of Chemistry, it was evidenced that the language used for the explanation of this phenomenon of interest in the scientific and technological community is very specific. Besides, it was observed the inexistence of a material to show an explanation, of the phenomena involved through a language that was accessible for beginners in the understanding of this state of the art. By these facts, this dissertation looked to do a transposition among the language, models and analogies used in scientific texts approaching the luminescence of composed of Eu3+ so that it turned easy the understanding and the construction of knowledge for the beginners in the subject. Tends in view the wide use of the luminescence of Eu3+ by the world scientific community and its vast range of technological applications as well as the lack of didactic materials with a more accessible language, mainly to the beginners in this research area, the objectives of this work were a rising of the terms used in summaries accepted for presentation in the Frogs of SBQ and dissertations and students' theories and teachers of the Group of Research in Chemistry of Materials of the University of Franca (Unifran), concerning the phenomenon of the luminescence. Soon afterwards it was developed a didactic material that contemplated an explanation with a more accessible language of the terms specifically used in scientific works involving luminescence of composed of Eu3+. Finally, it was decided the construction of a model with bisque mass for orbital f and the proposal of an explanation on the phenomenon of luminescence of Eu3+ through this model. key word: luminescence; teaching; concepts; languages; models; europium.